The effective outsourcing of building retrofitting: key decisions and motivators. Issue 4 (2nd September 2019) - Fasna, M.F.F.; Gunatilake, Sachie
Abstract : Purpose: Despite their energy conservation potential, still existing buildings are slow in embracing building energy efficiency retrofits (BEER), mainly because of the absence of a clearly defined process to deliver the BEER projects, and the lack of proactive guidance for project teams. Further, the identification of factors that can facilitate BEER projects is also important to ensure the project success. This is particularly true in energy service company (ESCO)-led projects. Hence, this study aims at investigating the decision-making process, including the motivators for the successful execution of each stage in implementing BEER when projects are outsourced to a third party. Design/methodology/approach: An in-depth case study was carried out to investigate the decision-making process and motivators in implementing BEER in a selected hotel building. Seven semi-structured interviews were conducted to collect the required data within the case. Findings: Study disclosed the 13 key decisions made and 37 key activities performed in each stage of the project. A total of 19 motivators for the successful execution of the respective stages were also elicited. Ultimately, the research findings are mapped against the five key stages of BEER decision-making process. Originality/value: The outcome of this study will provide the industry practitioners a basis for the effective adoption and implementation of BEER in existing hotel buildings when an external contractor is involved.